PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 014 BASILAM BARU - Alpusari, Mahmud Alpusari Mahmud; ', Hotmauli; ', Munjiatun (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract., Background problem in this study is the result of fourth grade students learn science SDN 014 Basilam Baru Kecamatan Sungai Sembilang Dumai is still low or inadequate standards KKM Only 5 people who completed the traditional fashion. For the research study conducted by Application Type STAD Cooperative Learning Model. With the formulation of the problem